Rancang Bangun Sistem Informasi Apotek Berbasis Website di Apotek Qta Farma Sumedang - Encep Supriatna; Shinta Devi Permata (Ma'soem University, 2022)
The design of a website-based pharmacy information system is a system created to enter data on products sold in pharmacies so that inventory and drug expiration periods can be controlled. For system design using the OOAD (object Oriented Analysis and Design) method while the model used is RUP (Rational Unified Process) with the development tool in the form of UML (Unified Modeling Language). There is also an explanation of the information system design process. Website-based pharmacies to be built, starting from the design of use case diagrams, activity diagrams, sequence diagrams, Class diagrams, User interfaces, hardware design and in hardware design this requires hardware configuration, specifications. hardware and software specifications.